2020
DOI: 10.3390/pharmaceutics12080769
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Pectin-Liposome Formulation against Multi-Resistant Bacterial Strains

Abstract: This work describes the development of a gastroresistant antimicrobial formulation composed of two carriers, pectin and liposomes, intended to improve the efficiency of norfloxacin (NOR) against multi-resistant bacterial strains. The formulations showed physicochemical stability for 180 days (4 °C) in terms of size, polydispersity, and zeta potential of the vesicles, prolonging the in vitro release of NOR for 11 h. The hybrid nanocarriers improved the in vitro antimicrobial activity against different multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…However, blood samples collected in research with CE do not always allow this analysis because it is not easy and takes time. Therefore, alternatives samples have been used to assess these parameters, such as amniotic fluid and allantoic fluid (5,7,46). In this work, we compared the biochemical analyses of serum and allantoic fluid and observed that the values found for the two samples were not always similar.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, blood samples collected in research with CE do not always allow this analysis because it is not easy and takes time. Therefore, alternatives samples have been used to assess these parameters, such as amniotic fluid and allantoic fluid (5,7,46). In this work, we compared the biochemical analyses of serum and allantoic fluid and observed that the values found for the two samples were not always similar.…”
Section: Discussionmentioning
confidence: 98%
“…Then, the embryo and yolk were weighed immediately after collecting blood and allantoic fluid on the day of collection. As the embryo weight is related to the initial egg weight, we performed an adjustment for an initial egg weight of 50 grams, according to Ribeiro et al (2020) (7) 2.4.…”
Section: Weight Of the Ce And Annexesmentioning
confidence: 99%
“…However, blood samples collected in research with CE do not always allow this analysis because it is not easy and takes time. Therefore, alternatives samples have been used to assess these parameters, such as amniotic uid and allantoic uid 5,7,33 . In this work, we compared the biochemical analyses of serum and allantoic uid and observed that the values found for the two samples were not always similar.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the embryo and yolk were weighed immediately after collecting blood and allantoic uid on the day of collection. As the embryo weight is related to the initial egg weight, we performed an adjustment for an initial egg weight of 50 grams, according to Ribeiro et al (2020) 7…”
Section: Weight Of the Ce And Annexesmentioning
confidence: 99%
See 1 more Smart Citation